Implications of the human immunodeficiency virus test and treat strategy on antiretroviral treatment uptake and retention outcomes in Cameroon - Awoh, Rogers A.; Ekane, Halle G.; Dzudie, Anastase; Thomas, Egbe O.; Adedimeji, Adebola; Jules, Assob N. (International Journal Of Community Medicine And Public Health, 2019)
Background: Success of the human immunodeficiency virus (HIV) test-and-treat (T&T) strategy requires high antiretroviral (ART) uptake and retention. However, low ART uptake and retention continue to be reported in ART programs. This study assessed ART uptake and retention outcomes of the HIV T&T strategy in three HIV clinics in Cameroon. Methods: A retrospective chart review was done for 423 patients who initiated HIV care within a period of three months prior to the implementation of the HIV T&T strategy, and for another 423 patients who initiated HIV care within a three-month period following the HIV T&T strategy implementation. For each group, sociodemographic, ART uptake and retention data were collected. Chi square and Student T tests were used to test for differences proportions and means between the two groups at p <0.05 and 95% confidence interval. Results: The mean ages (years) in the pre-T&T and the T&T groups were 39.73 and 39.72, and the proportion of female were 65.85% and 65.08% respectively. ART uptake proportion was higher amongst those enrolled under the T&T strategy (98.08% vs 95.39%, p=0.02). A greater proportion of the patients in the T&T group initiated ART within 2 weeks following HIV diagnosis (55.84% vs 48.17%, p=0.03). However, ART retention at 24th month was lower in the T&T group (78.83% vs. 85.79%, p=0.01). Conclusions: The findings suggest that the T&T strategy is associated with higher ART uptake, earlier ART initiation, and lower ART retention. This underscores a need for strategies to improve ART retention under the HIV T&T guidelines.